An Investigation on Peer Assessment: Teaching Text Summarization in English - Guskova, Natalia V. (Journal of History Culture and Art Research, 2019)
This paper discusses the specifics of using the method of peer assessment in the process of learning a brief text summary in English by the students of non-linguistic specialties. In particular, the effectiveness and expediency of using peer assessment in teaching foreign languages are analyzed by the author. The empirical part of the research was conducted at the National Research University Higher School of Economics (Moscow, Russia), with a group of undergraduate students studying at the Faculty of Economics. The author relied on a well-developed methodological apparatus, with the purpose of obtaining the most accurate and reliable data and conducting an objective analysis. As a result, the author concludes that the method of peer assessment can solve a number of pedagogical problems: increasing responsibility and autonomy of students; providing a deeper understanding of the subject; developing learning skills; stimulating each student to become an active worker and appraiser; developing critical thinking, etc. In addition, the method of peer assessment focuses on the maximum involvement of students in the learning process, which contributes to better learning motivation. More than that, it develops a supportive learning environment, in which our students could feel comfortable and fully trust each other and their teachers. The research results can be used to develop a more effective methodology for teaching foreign languages at non-linguistic specialties, as well as for conducting further research on related topics.